Design Thinking with ICT Tools: An Approach to Enhance Engagement in Design Problem and Practical Exposure - Chavan, Pruthviraj C.; Patil, Ajinkya K.; Chate, Ganesh R.; Malik, Vinayak R. (Journal of Engineering Education Transformations, 2025)
Students were unable to gain exposure to think practically, solve real-world problems, and think critically in recent years following pandemic situations, so design thinking is a rapid change in engineering education strategies to increase students’ engagement in imparting knowledge and skills remotely to the students. The traditional approach to teaching-learning strategies has given way to some advanced methods utilizing various modern approaches such as design thinking. The engagement of students actively and learning collaboratively with thinking ability is the major challenge in the learning of courses like metrology. The paper is a report on the author’s use of the design thinking approach for the learning and active participation of third-year mechanical engineering students at Rajarambapu Institute of Technology in Rajaramnagar. This paper describes the use of the design thinking approach for the metrology course and summaries of students’ active participation and improvement in terms of students’ "Learning Coefficient (LC)" based on the responses collected. The learning coefficient is represented by a number ranging from 0 to 1, with 0 indicating fewer interactive sessions and 1 indicating extremely interactive sessions. These coefficients reveal how much learning is taking place. Furthermore, the impact assessment shows that course results and course outcome attainment were significantly improved. The students’ feedback indicates that they had a great time and appreciated the opportunity to learn.